A pragmatic analysis of linguistic manipulative statements displayed on Facebook political group page - Brown, Papiso Irene; Molete, Mantoa (Journal of Applied Studies in Language, 2024)
This study investigates the pragmatic dimensions of linguistic manipulative statements found in Facebook political group pages, with a particular focus on the Hoatiti group. Social media platforms like Facebook have become powerful tools for political discourse, where language can be intentionally used to manipulate users' perceptions, beliefs, and actions. It examines how specific linguistic features are employed to sway opinions and promote particular ideologies within the group. Through qualitative analysis of posts and discussions on the Hoatiti group page it uses a purposive sample of n=5 statements, to identify patterns of language manipulation, misinformation, and loaded questions. The study also explores the socio-pragmatic context of these manipulative statements, examining how the interaction between the writer, the reader, and the political environment shapes the effectiveness of such discourse. This is a case study analysing how language is used strategically to manipulate Facebook users. Findings revealed that manipulation in political language, while not always overt, can occur through the use of specific pragmatic techniques including speech acts, among others. Through the lens of pragmatics, this research uncovered how these techniques were employed on Facebook and how they contributed to creating a persuasive and often manipulative environment. Findings revealed that subtle, yet powerful role of language influenced political thought on Facebook and provides insight into the broader implications of digital political communication. It is therefore, recommended that insights from such studies could inform the development of counter-narratives  through public awareness campaigns to protect individuals from being emotionally manipulated.